Latent profile analysis of post-traumatic growth and psychological resilience among patients with mental illness during the rehabilitation period: associations with social support - Yang, Zifei; Gu, Jianing; Yao, Xiuyu; Wang, Lina; Shao, Jing (Frontiers in Psychiatry, 2026)
BackgroundThe rising number of people affected by mental health disorders contributes to a significant disease burden and presents a major public health challenge worldwide. The purpose of the present study was to explore profiles of post-traumatic growth (PTG) and psychological resilience in rehabilitation patients with mental health disorders, and to analyze the effects of social support reported by these individuals.MethodsA convenience sampling method was employed to recruit 273 patients (Mage = 37.57, SD = 12.82) hospitalized in a psychiatric specialty hospital, from August to October 2024. Participants provided data through self-report instruments, including a general information questionnaire, the Post-traumatic Growth Inventory (PTGI), the Connor-Davidson Resilience Scale (CD-RISC), and Multidimensional Scale of Perceived Social Support (MSPSS), with all items from each scale administered. Latent profile analysis was conducted to explore the potential categorization of PTG and psychological resilience; multifactorial logistic regression was used to analyze its influencing factors; and ANOVA was used to compare differences in social support level reported by patients with different categories of PTG and psychological resilience.ResultsMeasures of CD-RISC and PTGI displayed substantial heterogeneity, and were therefore divided into three groups: severe turmoil (13.3% of participants), fluctuating adaptation (53.6%), and integrated adaptation (33.1%). Regression analysis showed that age and social support were factors that significantly influenced classification (P < 0.05), and comparison of social support scores among patients in the three groups showed significant differences (P < 0.05).ConclusionHeterogeneity existed in the PTG and psychological resilience of patients during the rehabilitation period. Compared with other subgroups, patients in the integrated adaptation group exhibited elevated social support resources. Healthcare professionals should utilize these groups when assessing PTG and resilience. This will allow for personalized clinical interventions based on these profiles that may help ameliorate psychological distress, increase perceived social support, and enhance overall mental well-being.